Implementasi kurikulum berbasis Tarbiyatul Muallimin Al Islamiyah dalam meningkatkan kualitas dan kapabilitas santri di Pondok Pesantren - Cahyono, Gangsar; Aljauhari, Shofwan; Yulia Rahman, Hendra (IAIN PAREPARE, 2023)
The implementation of the curriculum based on the values of Tarbiyatul Muallimin Al Islamiyah at Annajah Yamra Merauke Islamic boarding school by emphasizing the integration of the daily attitudes and behavior of students can run well as the vision and mission of education. However, this context tends to be neglected in scientific discussions. The study in addition to complementing the shortcomings of the studies that have been done, also focuses on the question